Progress in LRRK2-Associated Parkinson’s Disease Animal Models - Seegobin, Steven P.; Heaton, George R.; Liang, Dongxiao; Choi, Insup; Blanca Ramirez, Marian; Tang, Beisha; Yue, Zhenyu (Frontiers in Neuroscience, 2020)
Mutations in the leucine-rich repeat kinase 2 (LRRK2) gene are the most frequent cause of familial Parkinson’s disease (PD). Several genetic manipulations of the LRRK2 gene have been developed in animal models such as rodents, Drosophila, C. elegans, and zebrafish. These models can help us further understand the biological function and derive potential pathological mechanisms for LRRK2. Here we discuss common phenotypic themes found in LRRK2-associated PD animal models, highlight several issues that should be addressed in future models and discuss emerging areas to guide their future development.